2007
DOI: 10.1158/0008-5472.can-07-1811
|View full text |Cite
|
Sign up to set email alerts
|

In vivoTargeting of Human Neutralizing Antibodies against CD55 and CD59 to Lymphoma Cells Increases the Antitumor Activity of Rituximab

Abstract: An in vivo model of human CD20+ B-lymphoma was established in severe combined immunodeficiency mice to test the ability of human neutralizing miniantibodies to CD55 and CD59 (MB55 and MB59) to enhance the therapeutic effect of rituximab. The miniantibodies contained single-chain fragment variables and the hinge-CH2-CH3 domains of human IgG 1 . LCL2 cells were selected for the in vivo study among six B-lymphoma cell lines for their high susceptibility to rituximab-dependent complement-mediated killing enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 48 publications
(61 reference statements)
7
136
0
Order By: Relevance
“…25 Extensive evidence indicates that the high expression of mCRPs on the cancer cells influences the efficacy of the rituximab-mediated CDC effect. 39 Consistently, we also demonstrated that the high level of CD59 expression was the major cause of lymphoma resistance to rituximab. CD59 mAb may effectively improve the immunotherapeutic result induced by rituximab.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…25 Extensive evidence indicates that the high expression of mCRPs on the cancer cells influences the efficacy of the rituximab-mediated CDC effect. 39 Consistently, we also demonstrated that the high level of CD59 expression was the major cause of lymphoma resistance to rituximab. CD59 mAb may effectively improve the immunotherapeutic result induced by rituximab.…”
Section: Discussionsupporting
confidence: 77%
“…CD59 mAb may effectively improve the immunotherapeutic result induced by rituximab. 39 Meanwhile, in an effort to enhance the efficacy of mAb-induced immunotherapies in other tumor cell lines, a variety of methods, such as Ab, siRNA and peptide treatments, have been used to neutralize or decrease the expression of CD59. [40][41][42] However, these treatments often produce multiple side effects because they target both tumor cells and normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing or inactivating CD55 is an effective idea to restore the therapeutic effect of rituximab. 8 In our present analyses, the level of CD55 significantly decreased 12-24 h after CMC-544 exposure. It is consistent with the observation that CDC from rituximab increased 12 h after incubation with CMC-544.…”
Section: Discussionsupporting
confidence: 51%
“…2,8,9 Among them, CMC-544 has been introduced as a promising agent to treat refractory/resistant BCM. CMC-544 is a conjugate of N-acetyl g-calicheamicin dimethyl hydrazide (NAc g-calicheamicin DMH) and a recombinant humanized antibody (IgG 4 ) directed against the CD22 antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Although the miniAbs failed to activate complement alone, they killed about 25% cells through ADCC. 142,143 (ii) Peptides derived from C8 and C9: extensive studies of hCD59 structure, as well as of its interaction with C8 and C9, revealed the region of hCD59 critical for inhibiting MAC formation through preventing binding of C8 and C9. [144][145][146][147][148] Small peptides derived from C8 and C9 that bind to this region are effective against hCD59 function at concentrations greater than 300 mmol/l of IC 50 , limiting their therapeutic usefulness.…”
Section: Complement Activation In Hiv-1 Infection Qg Yu Et Al 336mentioning
confidence: 99%